Genome-Wide Identification of Calcium-Dependent Protein Kinases in Chlamydomonas reinhardtii and Functional Analyses in Nitrogen Deficiency-Induced Oil Accumulation - Li, Yajun; Fei, Xiaowen; Dai, Haofu; Li, Jiangyue; Zhu, Weiju; Deng, Xiaodong (Frontiers in Plant Science, 2019)
Calcium-dependent protein kinases (CDPKs) are recognized as important calcium (Ca2+) sensors in signal transduction and play multiple roles in plant growth and developmental processes, as well as in response to various environmental stresses. However, little information is available about the CDPK family in the green microalga Chlamydomonas reinhardtii. In this study, 15 CrCDPK genes were identified in C. reinhardtii genome, and their functions in nitrogen (N) deficiency-induced oil accumulation were analyzed. Our results showed that all CrCDPK proteins harbored the typical elongation factor (EF)-hand Ca2+-binding and protein kinase domains. Phylogenetic analysis revealed that these CrCDPKs were clustered into one group together with a subclade of several CPKs from Arabidopsis and rice, clearly separating from the remaining AtCPKs and OsCPKs. These genes were located in 10 chromosomes and one scaffold of C. reinhardtii and contained 6–17 exons. RNA sequencing and quantitative reverse transcription (qRT)-PCR assays indicated that most of these CrCDPKs were significantly induced by N deficiency and salt stress. Lanthanum chloride (LaCl3), a plasma membrane Ca2+ channel blocker, limited oil accumulation in C. reinhardtii under N-deficient conditions, suggesting that Ca2+ was involved in N deficiency-induced oil accumulation. Furthermore, RNA interference (RNAi) silencing analyses demonstrated that six CrCDPKs played positive roles and three CrCDPKs played negative roles in N deficiency-induced oil accumulation in C. reinhardtii.